BARLIQ KÁSIPLERDIŃ TIYKARI - Allaniyazov, Ismail Begjanovich; Ismaylova, Aziza Saadatdin qızı (SCIENCE and SOCIETY, 2026)
The article is dedicated to the social significance of the teaching profession, with substantiated facts presented.